2014
DOI: 10.4236/wja.2014.41008
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure, Multiple Sex Partners, and Consistent Condom Use among HIV Positive Adults on Antiretroviral Therapy in Johannesburg, South Africa

Abstract: Inconsistent condom use among persons on antiretroviral treatment (ART) is a major public health concern because of the risk of HIV transmission. This study examined the association between socio-demographic variables and knowing partners' HIV status, multiple sex partners, and consistent condom use among 400 HIV-infected adults who had received ART for at least six months in Johannesburg, South Africa. The study used a cross-sectional survey and a structured interviewer administered questionnaire. Over half (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
8
10
0
Order By: Relevance
“…In this study, more than a third, 38% (95% CI: 33.3%, 42.3%), of the study participants had risky sexual practice in the past three months preceding data collection. This finding is consistent with studies conducted in Addis Ababa (36.9%)[8], (30.4%)[11], South Africa, Johannesburg (34.0%)[12], and Togo (34.6%)[13]. However, the finding is higher than those of studies done in Debrezeit, Ethiopia (22.2%)[5], and Kenya (28%)[14].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, more than a third, 38% (95% CI: 33.3%, 42.3%), of the study participants had risky sexual practice in the past three months preceding data collection. This finding is consistent with studies conducted in Addis Ababa (36.9%)[8], (30.4%)[11], South Africa, Johannesburg (34.0%)[12], and Togo (34.6%)[13]. However, the finding is higher than those of studies done in Debrezeit, Ethiopia (22.2%)[5], and Kenya (28%)[14].…”
Section: Discussionsupporting
confidence: 88%
“… 17 , 18 Another study conducted in Johannesburg, South Africa, also indicated that participants who were aware of their partner’s HIV status were 4 times more likely to use condoms in a consistent manner than those who were not. 19 This might be due to the possibility that PLHIV who did not know their partners’ status might not push to use condom during sex.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of transmission of drug-resistant virus to discordant, concordant and HIV serostatus negative people is evidenced by a significant number of HIV patients on ART engaging in unprotected sex. A study done in South Africa depicted that 34.0% having multiple sex partners and 24.2% having unprotected sex among people living with HIV on ART [ 14 ]. A study conducted in Kenya showed unprotected sex occurred in 52% of sexual partnerships with 32% of HIV-negative partners and 54% of partners of unknown HIV status in the last 6 months [ 2 ].…”
Section: Introductionmentioning
confidence: 99%